2011
DOI: 10.1016/j.semarthrit.2011.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Work Disability in Patients with Systemic Sclerosis: A Longitudinal Study of the GENISOS Cohort

Abstract: Objectives To determine the prevalence, correlates, and predictors of work disability (WD) in the Genetics versus ENvironment In Scleroderma Outcome Study (GENISOS). We hypothesized that WD in systemic sclerosis (SSc) is a function of demographic, clinical, and psychosocial factors. Methods Patients enrolled in the GENISOS cohort were subdivided in 3 groups: work disabled, working, and retired or homemakers. The latter group (n=29) was excluded from further analysis. We used logistic regression analysis with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 45 publications
3
33
0
2
Order By: Relevance
“…The dependent variable was a categorical measure of labor force participation indicating whether a person was a full‐time employee, a part‐time employee, or not in the labor force. By using the number of hours worked per week a study participant reported, full‐time employment was defined as 40 or more hours worked per week (Benda, Toombs, & Corwyn, ; Sharif et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…The dependent variable was a categorical measure of labor force participation indicating whether a person was a full‐time employee, a part‐time employee, or not in the labor force. By using the number of hours worked per week a study participant reported, full‐time employment was defined as 40 or more hours worked per week (Benda, Toombs, & Corwyn, ; Sharif et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…Increasingly, attention has been drawn to the problem of work incapacity in patients with SSc. Sharif et al have demonstrated incapacity for work in 43.7% of patients already at an early stage of systemic sclerosis [12]. Consequently, it is essential to provide patients with comprehensive and individually adjusted therapy.…”
Section: Wstępmentioning
confidence: 99%
“…Sharif i wsp. wykazali niezdolność do pracy u 43,7% pacjentów już we wczesnym okresie SSc [12]. Dlatego konieczne jest prowadzenie kompleksowej i indywidualnie dobranej terapii.…”
Section: Hand Rehabilitationunclassified
“…It is a major contributor of disability in SSc, paralleling that of patients with cancer undergoing chemotherapy 58,59 .…”
Section: Manifestations and Complicationsmentioning
confidence: 99%